2022
DOI: 10.1016/j.ijso.2022.100512
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of complicated appendicitis during the COVID-19 pandemic: A systematic review and meta-analysis

Abstract: Introduction: Measures taken to prevent the spread of coronavirus disease 2019 (COVID-19) slow surgical processes, and patients are avoiding presenting at emergency departments during the outbreak because of fears of contracting the contagious disease. To analyze the rate of complicated appendicitis before and during the COVID-19 pandemic. Methods: We systematically reviewed the PubMed and SCOPUS databases for articles published from 2000 to 2021. Inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
2
11
1
1
Order By: Relevance
“…They suggested that the reason for this delay is patient concern about COVID-19 transmission at the hospital. However, the finding that the time between symptom onset and emergency department visit remained unchanged in other studies was consistent with ours [ 20 21 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…They suggested that the reason for this delay is patient concern about COVID-19 transmission at the hospital. However, the finding that the time between symptom onset and emergency department visit remained unchanged in other studies was consistent with ours [ 20 21 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…During the pandemic we identified a statistically significant increase in the rates of complicated appendicitis. A rise in the number of patients presenting with complicated appendicitis has also been demonstrated in other studies [ 33 , 34 ], with reported increased relative risk of 1.55 in a meta-analysis of 3559 patients [ 36 ]. We believe the significant increase in complicated appendicitis can account for the significant increase in rates of caecectomy and intraoperative insertion of drains.…”
Section: Discussionsupporting
confidence: 57%
“…A large number of studies and meta-analyses have reported an increase in the proportion of complicated appendicitis during the Covid-19 pandemic, suggesting increased delay as explanation [1][2][3][4][5][6][7]. Some studies also report a concomitant decrease in the number of uncomplicated appendicitis, suggesting that undiagnosed uncomplicated appendicitis may resolve without treatment due to the restrained access to health care [4].…”
Section: Introductionmentioning
confidence: 99%
“…As the proportion of complicated appendicitis is determined by the number of complicated appendicitis as numerator and the total number of patients with appendicitis as denominator, the concomitant decrease in the number of patients with uncomplicated appendicitis must also have had an impact [4]. It is known that variations in the incidence rate of uncomplicated appendicitis are more closely associated with the proportion of complicated appendicitis [8], whereas the impact of the Covid pandemic on the proportion of complicated appendicitis has been analyzed in several meta‐analyses we have not seen any previous analysis of the impact on the incidences of complicated and uncomplicated appendicitis separately [2–7].…”
Section: Introductionmentioning
confidence: 99%